Zinc-Doped Antibacterial Coating as a Single Approach to Unlock Multifunctional and Highly Resistant Titanium Implant Surfaces - Malheiros, Samuel S.; Borges, Maria Helena R.; Rangel, Elidiane C. [UNESP]; Fortulan, Carlos A; da Cruz, Nilson C. [UNESP]; Barao, Valentim A. R.; Nagay, Bruna E. (American Chemical Society (ACS), 2025)
Failures of dental and orthopedic implants due to microbial colonization, corrosion, and insufficient osseointegration remain persistent clinical challenges. Current implant surface coatings often lack the mechanical robustness needed for long-term success. Therefore, this study developed zinc (Zn)-doped coatings on titanium implants via plasma electrolytic oxidation (PEO), achieving 11 at % Zn incorporation primarily as zinc oxide (ZnO). The Zn-doped coatings were primarily composed of zinc, calcium, phosphorus, and oxygen, displaying moderate roughness (∼1 μm), hydrophilic behavior, and high crystallinity with anatase and rutile phases. Tribological tests demonstrated over a 50% reduction in mass loss, while electrochemical tests confirmed significantly enhanced corrosion resistance of Zn-doped coating with higher open circuit potential values, larger Nyquist plot semicircles, and higher impedance values at low frequencies compared to controls (p < 0.05). The Zn-doped coatings also showed superior antimicrobial efficacy, reducing Streptococcus sanguinis viability, completely inhibiting Escherichia coli growth, and reducing biofilm biomass by over 60%, which may be related to the sustained Zn release (∼6 μg/cm2) over 7 days. Enhanced bioactivity was evidenced by greater protein adsorption, increased hydroxyapatite formation, and improved preosteoblastic cell metabolism and morphology. Ex vivo analyses confirmed coating mechanical stability, without morphological or chemical impairment, during implant insertion and removal from bovine rib bone, with increased implant stability quotient (ISQ) values, indicating benefits in poor bone quality. These findings highlight the significant promise of Zn-doped plasma electrolytic oxidation coatings for advancing dental and orthopedic implant technology, offering enhanced longevity, antimicrobial defense, and improved bioactivity to optimize clinical outcomes.
Keywords: bioactive coatings; biofilms; biomaterials; corrosion; dental implant; plasma electrolytic oxidation; proteins; zinc